MEMBANGUN KELUARGA BAHAGIA: NILAI-NILAI INTERAKSI SUAMI ISTRI DALAM AL-QUR’AN - Ana Rahmawati; Alfina Fairuz Zakiya; Helmy Zulia Rahmawati; Vera Kurnia Hapsari (CV. Adiba Aisha Amira, 2024)
By examining the values of husband-wife interaction in the Qur'an as a foundation for building a happy family, this study raises the question of how the Qur'an provides guidance and attitudes regarding the relationship between men and women in the family. The research findings show that the Qur'an emphasizes the values of love, justice, mutual understanding, and responsibility for both husband and wife as parents to achieve family happiness. The conclusion of this study is that the application of the interaction values between men and women taught in the Qur'an will have a positive impact on harmony and happiness within the family.